Town of Forest comprehensive planning public opinion survey report, 2008 - Janke, James; Trechter, David; Hadley, Shelly (My University, 2009)
The purpose of this survey was to understand public opinions about a range of important land use issues facing the Town of Forest in Saint Croix County. Survey results will provide input into the comprehensive land use plan for the town.
33 p.
Keywords: Survey; University of Wisconsin-River Falls. Survey Research Center; UWRF Survey Research Center Report; Public opinion survey; Community planning; Comprehensive plan report; Comprehensive plan; Town of Forest comprehensive plan; Saint Croix County, Wisconsin; Saint Croix County (Wis.); Town of Forest; Forest (Saint Croix County, Wis. : Town); Forest (Saint Croix County, Wis. : Town)--Surveys; Public opinion--Wisconsin--Forest (Saint Croix County : Town); Land use--Wisconsin--Forest (Saint Croix County : Town); City planning--Wisconsin--Forest (Saint Croix County : Town)